Petal to the metal - Tobin, Paul; Chan, Ron; Dutro, Steve; Rainwater, Matthew J. (Milwaukie, OR Dark Horse Books, 2016)
When Crazy Dave challenges Zomboss to a series of challenges for the fate of Neighborville, the zombies and plants take to the road in a series of car-filled competitions.
Petal to the metal -- The lady in red / art by Brian Churilla.
"Collects the stories found in Plants vs. Zombies #7-#9: Petal to the Metal Parts 1-3 and Plants vs. Zombies: The Lady in Red short story that appeared in Free Comic Book Day 2016: all ages"--Title page verso.
Based on the video game Plants vs. Zombies.
Accelerated Reader AR
115090
Keywords: Zombies -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Juvenile Fiction -- Comics & Graphic Novels -- Media Tie-In.; Plants -- Comic books, strips, etc; Automobile racing -- Comic books, strips, etc; Science fiction comic books, strips, etc; Plants -- Fiction; Science fiction; United States; Science fiction comic books, strips, etc; comic books; comic strips; Novels; Science fiction comics; Fiction; Comics (Graphic works); Graphic novels